2014
DOI: 10.1123/jsep.2013-0261
|View full text |Cite
|
Sign up to set email alerts
|

Goal Striving and Well-Being in Sport: The Role of Contextual and Personal Motivation

Abstract: 1This investigation sought to clarify mixed results in the literature exploring coach behaviors, 2 basic psychological needs, goal motivation, and well-and ill-being. Regional level team sport 3 athletes (N = 241) completed questionnaires on the aforementioned variables at the beginning 4 of the season. A subsample (n = 70) provided saliva samples to assess physical ill-being. At 5 the end of the season, athletes (n = 98) reported their goal motivation and attainment. 6Structural equation modeling demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 53 publications
3
50
0
1
Order By: Relevance
“…Goal intentions of external and introjected modes are categorised as non-selfconcordant. They are considered to provide an unstable basis for sustained goal pursuit because persons do not fully adhere to their goals (Healy, Ntoumanis, van Zanten, & Paine, 2014). Goal intentions of identified and intrinsic modes are classified as self-concordant.…”
Section: Modes Of Self-concordancementioning
confidence: 99%
“…Goal intentions of external and introjected modes are categorised as non-selfconcordant. They are considered to provide an unstable basis for sustained goal pursuit because persons do not fully adhere to their goals (Healy, Ntoumanis, van Zanten, & Paine, 2014). Goal intentions of identified and intrinsic modes are classified as self-concordant.…”
Section: Modes Of Self-concordancementioning
confidence: 99%
“…Actualmente, en el ámbito deportivo, los estudios realizados con el BNSSS están enfocados a relacionar las necesidades psicológicas básicas con diversas variables poco relacionadas con características demográficas o deportivas, como son: engagement y antipatía (Curran, Hill y Niemic, 2013;Curran, Hill, Hall y Jowett, 2014;Curran, Hill, Ntoumanis, Hall y Jowett, 2016); experiencia, diálogo interno y estado de flow (Delrue, Mouratidis, Haerens, de Muynck, Aelterman y Vansteenkiste, 2016); clima motivacional (Hodge y Gucciardi, 2015;Morela, Hatzigeorgiadis, Sanchez, Papaioannou y Elbe, 2017), autoridad del entrenador (Brinton, Hill y Ward, 2017); bienestar, metas de logro y conducta del entrenador (Healy, Ntoumanis, van Zanten y Paine, 2014;Pope y Wilson, 2014); perfeccionismo, burnout y engagement ; liderazgo y bienestar (Stenling y Tafvelin, 2014, Stenling, Lindwall y Hassmén, 2015; y, burnout (Li, Wang y Pyun , 2017), entre otros.…”
unclassified
“…We included in the analysis the four 21 motivation regulations for each goal; eight variables were used in total. This approach is different to 22 previous SC model research 3,4,11 , where the extrinsic and introjected, and identified and intrinsic 23 scores have been aggregated to form controlled and autonomous goal motives respectively. Our 24 approach was based on two reasons.…”
mentioning
confidence: 99%
“…First, the four items represent separate (albeit related) motivation 25 regulations. Additionally, previous research has often found these goal motives aggregates to have 26 poor internal reliability 3,11 . Unlike previous studies, in our analyses we were unable to correct for 27 GOAL MOTIVATION AND MULTIPLE GOAL STRIVING 6 measurement error.…”
mentioning
confidence: 99%